2014
DOI: 10.1093/rheumatology/keu379
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness is more than just duration and severity: a qualitative exploration in people with rheumatoid arthritis

Abstract: Objective. Stiffness is internationally recognized as an important indicator of inflammatory activity in RA but is poorly understood and difficult to measure. The aim of this study was to explore the experience of stiffness from the patient perspective.Methods. Semi-structured interviews conducted with 16 RA patients were analysed independently by researchers and pat.ient partners using inductive thematic analysis.Results. Six themes were identified. Part of having RA identified stiffness as a normal consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 33 publications
1
43
0
3
Order By: Relevance
“…Two qualitative studies were conducted by members of our group to further explore the experience of stiffness in RA (10, 11). Similar themes were identified in both studies and incorporated into conceptual frameworks encompassing the heterogeneous experience of stiffness impact, intensity, timing, location and duration in people with RA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two qualitative studies were conducted by members of our group to further explore the experience of stiffness in RA (10, 11). Similar themes were identified in both studies and incorporated into conceptual frameworks encompassing the heterogeneous experience of stiffness impact, intensity, timing, location and duration in people with RA.…”
Section: Discussionmentioning
confidence: 99%
“…The stiffness question, developed by the Flare Steering Committee, asked people to “Circle the number than best describes the stiffness you have felt due to your rheumatoid arthritis during the past week” (0-10 numeric rating scale where 0 = none and 10 = extreme). Two break-out groups were held to discuss these results and new qualitative studies conducted in the US and UK (10, 11) in relation to stiffness measurement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from focus groups with 20 participants (USA; (23)) and 16 individual interviews (UK; (24)) were presented. Findings suggested that people with RA described the experience of stiffness in terms of severity and impact throughout the day, rather than as the duration of morning symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with arthritis frequently report symptoms such as morning pain and stiffness, leading to limitations at a functional level and impaired quality of life [1,[3][4][5]. It is therefore logical that therapeutic interventions for arthritis would specifically target this period of the day and that any evaluation of their efficacy would focus on their direct impact on morning pain and stiffness [6].…”
Section: Introductionmentioning
confidence: 99%